Water use and production of processing tomato under no-tillage system and straw mulching conditions - Marouelli, Waldir Aparecido; da Silva, Henoque Ribeiro; Madeira, Nuno Rodrigo (Pesquisa Agropecuaria Brasileira, 2006)
The work aimed to evaluate the effect of straw rates (3, 6, and 9 t ha-1 dry matter of sorghum forage), under no-tillage system, on crop water use and production of four processing tomatoes cultivars, as compared to conventional tillage system. The experimental design was the randomized blocks design with split plots and four replicates. Cultivars H9553 and H9992, in 2003, and H7155 and U2006, in 2004, were evaluated. The water use under no-tillage treatments during the first 50 days, since seedlings were transplanted, was 25% lower as compared to conventional tillage, and 11% lower during the entire crop season. Cultivars relative performance was equivalent for all evaluated variables. Marketable fruit yield was maximized at 6 t ha-1 straw, while rotten rate fruit was minimized at 5.2 t ha-1. Under conventional tillage system, fruit yield was 10 to 17% lower than under no-tillage treatments. Crop water use efficiency was not affected by cover crop rates, but no-tillage treatments yielded an average water use efficiency 23% higher than conventional tillage system.